Precision Frequency Measurement of 87Rb 5S1/2 (F = 2)→5D5/2 (F″ = 4) Two-Photon Transition through a Fiber-Based Optical Frequency Comb*Supported by the National Natural Science Foundation of China under Grant Nos 61405002, 91336103, 10934010, 61535001 and 61078026. (May 2016) - Xia 夏, Wei 巍; Dai 戴, Shao-Yang 少阳; Zhang 张, Yin 胤; Li 李, Kun-Qian 坤乾; Yu 于, Qi 齐; Chen 陈, Xu-Zong 徐宗
Abstract : The absolute frequency of 87 Rb 5S1/2 (F = 2)→5D5/2 (F″ = 4) two-photon transition at 778nm is measured in an accuracy of 44 kHz. A home-made erbium-doped fiber laser frequency comb with frequency stability of 5.0 × 10 −13 @1 s is employed for the light source. By using a periodically poled lithium niobate, the femtosecond pulse operating in 1556nm is frequency-doubled to 778nm to obtain the direct two-photon transition spectroscopy of thermal rubidium vapor. Through sweeping the carrier envelope offset frequency (fceo ), the 5S1/2 (F = 2)→5D5/2 (F″ = 4) two-photon transition line is clearly resolved and its absolute frequency is determined via the peak-finding of the fitting curve. After the frequency correction, the measured result agrees well with the previous experiment on this transition. The entire system configuration is compact and robust, providing a potential candidate of optical frequency standard for telecommunication applications.